Substance P Neurokinin 1 Receptor Activation within the Dorsal Raphe Nucleus Controls Serotonin Release in the Mouse Frontal Cortex - Guiard, Bruno P.; Guilloux, Jean-Philippe; Reperant, Christelle; Hunt, Stephen P.; Toth, Miklos; Gardier, Alain M. (Molecular pharmacology, 2007)
Preclinical studies suggest that substance P (SP) neurokinin 1 (NK1) receptor antagonists are efficient in the treatment of anxiety and depression. This therapeutic activity could be mediated via stimulation of serotonin (5-HT) neurons located in the dorsal raphe nucleus (DRN), which receive important SP-NK1 receptor immunoreactive innervations. The present study examined the effects of intraraphe injection of SP on extracellular 5-HT levels in the frontal cortex, ventral hippocampus, and DRN by using intracerebral microdialysis in conscious mice. Intraraphe SP injection dose dependently decreased cortical 5-HT release, whereas no effects were detected in the ventral hippocampus. Cortical effects were blocked by the selective NK1 receptor antagonist N-[[2-methoxy-5-[5-(trifluoromethyl)tetrazol-1-yl]phenyl]methyl]-2-phenylpiperidin-3-amine (GR205171) and completely dampened in mice lacking NK1 receptors. Furthermore, genetic (in knockout 5-HT1A-/- mice) or pharmacological inactivation of 5-HT1A autoreceptors blocked cortical responses to SP. Contrasting with its cortical effects, intraraphe SP injection increased 5-HT outflow in the DRN in wild-type mice; this effect was potentiated by a local perfusion of the selective 5-HT1A antagonist N-[2-[4-(2-methoxyphenyl)-1-piperazinyl]ethyl]-N-2-pyridinylcyclohexanecarboxamide (WAY100635). Finally, SP-induced changes in frontal cortex and DRN dialysate 5-HT levels were blocked by the DRN perfusion of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)/kainate ionotropic receptor antagonist 6,7-dinitroquinoxaline-2,3-dione (DNQX). These data support the hypothesis that SP-induced over-activation of 5-HT1A autoreceptors within the DRN limits cortical 5-HT release. A better knowledge of the complex relationship between tachykininergic, serotonergic, and glutamatergic systems within the DRN might help better understand the pathophysiology and subsequent treatment of depression.